Policy-driven food security: investigating the impact of China’s maize subsidy policy reform on farmer’ productivity - Ye, Feng; Qin, Shengze; Li, Huanjiao; Li, Zilin; Tong, Ting (Frontiers in Sustainable Food Systems, 2024)
China is the largest producer, consumer, and trader of grain. Changes in China's agricultural policies will affect global food trade and thus impact food security. In this paper, we use China's maize subsidy system reform(MSSR) as a quasi-natural experiment to investigate the impact of marketoriented reforms in price support policy on the productivity of grain. We use official Chinese government panel data on farm households and a PSM-DID model to overcome the endogeneity problem of policy change. The empirical results show that MSSR can increase maize productivity.The MSSR is divided into two phases: eliminating the maize purchase price and implementing maize producer subsidies. The policy effect of eliminating the purchase price exceeds the implementation of producer subsidies. Further analysis reveals that for farmers with a larger scale of cultivation, higher level of specialization, and higher degree of part-time employment, the MSSR enhances their productivity more significantly. In the high quartile, the MSSR reduces farmers' productivity. In the low quartile, the MSSR raises farmers' productivity, suggesting that the MSSR reduces the productivity differences among farmers. The results of our study suggest that market-based reform of price subsidies is an effective institutional arrangement to mitigate resource mismatch and increase food productivity, and point to the need to continue to improve the MSSR, explore diversified maize producer subsidy policies, and take into account the impact of other subsidies on farmers' maize production behavior.